SOCIAL PHYSIQUE ANXIETY AND BODY IMAGE SATISFACTION LEVELS OF COLLEGIAN DANCERS - Fatma Cepikkurt; Funda Coskun (Pamukkale University, 2010)
The purposes of this study were to investigate the relationship between Social Physique Anxiety (SPA) and Body Image Satisfaction (BIS) and to determine the differences in SPA and BIS between female and male dancers. Thirty nine female and twenty three male dancers from different faculties in Cukurova University were voluntarily participated in this study. "Social Physique Anxiety Scale" and "Body Image Satisfaction Questionnaire" were administered to participants. Data were analyzed by using descriptive statistics, independent t-test and Pearson correlation analysis. Pearson correlation analysis revealed negative correlation between BIS and "the expectation of negative evaluation of one's physique by others" subscales of SFA (r = -.57; p<0.05) and between BIS and "feeling of discomfort about one physique" subscales of SFA (r = -. 64, p<0.05). The t-test results revealed significant differences in "feeling discomfort about one physique" subscales of SPA between female and male dancers (t = .041; p<0.05). In conclusion, female dancers had more negative feelings about own physical appearance compared in male dancers.